2017
DOI: 10.1007/s10532-017-9813-x
|View full text |Cite
|
Sign up to set email alerts
|

A new aerobic chemolithoautotrophic arsenic oxidizing microorganism isolated from a high Andean watershed

Abstract: Biological arsenic oxidation has been suggested as a key biogeochemical process that controls the mobilization and fate of this metalloid in aqueous environments. To the best of our knowledge, only four aerobic chemolithoautotrophic arsenite-oxidizing (CAO) bacteria have been shown to grow via direct arsenic oxidation and to have the essential genes for chemolithoautotrophic arsenite oxidation. In this study, a new CAO bacterium was isolated from a high Andean watershed evidencing natural dissolved arsenic att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Microorganisms can interconvert As(III) and As(VI) and thus are capable of either solubilizing or immobilizing As in the soil-plant system [ 2 , 108 ]. These microbially induced biotransformations of As play important roles in the biogeochemical behavior of As and is key in risk assessment and remediation studies [ 109 ].…”
Section: Speciation Of Arsenic In Soilmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms can interconvert As(III) and As(VI) and thus are capable of either solubilizing or immobilizing As in the soil-plant system [ 2 , 108 ]. These microbially induced biotransformations of As play important roles in the biogeochemical behavior of As and is key in risk assessment and remediation studies [ 109 ].…”
Section: Speciation Of Arsenic In Soilmentioning
confidence: 99%
“…Microbially induced transformations of As from one from to another occurs via different processes/mechanisms such as methylation and demethylation (conversions of inorganic to organic forms and vice versa) [ 2 , 104 , 108 , 109 ]. It is reported that microorganisms can biomethylate inorganic As species to organic forms of As [ 116 ].…”
Section: Speciation Of Arsenic In Soilmentioning
confidence: 99%
“…Copper mining entails the production of arsenic compounds that are not only highly toxic, but also water‐soluble. In the project ReAK, scientists of Fraunhofer IWKS (Alzenau, Germany) together with their research partners in Germany and Chile are developing a more sustainable copper production process, using new technology approaches, such as microbial leaching, [26] sulfidic leaching and oxidative extraction. This approach not only does improve the efficiency of the process, but it also leads to more stable arsenic compounds that are safer to deposit.…”
Section: Inorganic Materials Chemistry As a Pillar For Circularity Inmentioning
confidence: 99%
“…Ancylobacter sp. TS‐1 is a recently isolated microorganism with the capacity to perform chemolithoautotrophic arsenic oxidation . The nucleotide sequence of 16S rDNA gene, and the aminoacid sequence of arsenite oxidase and RubisCO genes were submitted to NCBI under accessing numbers KX139404, KX250215, and KX250216, respectively .…”
Section: Figurementioning
confidence: 99%
“…TS‐1 is a recently isolated microorganism with the capacity to perform chemolithoautotrophic arsenic oxidation . The nucleotide sequence of 16S rDNA gene, and the aminoacid sequence of arsenite oxidase and RubisCO genes were submitted to NCBI under accessing numbers KX139404, KX250215, and KX250216, respectively . TS‐1 was isolated from a site with high iron, inorganic sulfur compounds (ISC) and arsenic content in a hydrothermal source in Northern Chile .…”
Section: Figurementioning
confidence: 99%